An Osmotic Computing Enabled Domain Naming System (OCE-DNS) for distributed service relocation between cloud and edge. (December 2021) - Sicari, Christian; Galletta, Antonino; Celesti, Antonio; Fazio, Maria; Villari, Massimo
Abstract: Osmotic computing has emerged as a solution enabling the Cloud–Edge–Internet of Things (IoT) continuum. It supports the transparent deployment of distributed services called Micro ELements (MELs) over these heterogeneous software layers guaranteeing application proximity to end-users. This paradigm is very useful for data mining processing of emerging future Internet applications because it allows optimizing both the response time and the usage of computational resources. In this paper, we focus on an approach for identifying MELs which serve a specific geographical area. In particular, we present the Osmotic Computing Enabled Domain Name System (OCE-DNS), an advanced DNS able to reference MELs using the Extended Plus Codes, a three dimensional geocode algorithm defined by us. Experiments show that OCE-DNS guarantees quick Resource Records (RR) readings and updates, thence supporting the management of transparent Osmotic MEL migrations.